2020
DOI: 10.2106/jbjs.20.00258
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gender Disparities in Authorship of Arthroplasty Research

Abstract: Background: Despite efforts to address gender disparities in medicine, female representation in orthopaedics lags behind that of other fields, and little work has evaluated gender disparities within the subspecialty of arthroplasty surgery. The objective of this study was to analyze female authorship trends in arthroplasty research from 2002 to 2019. Methods: Articles published from 2002 to 2019 in 12 clinical orthopaedic and arthroplasty journals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…A 90% cutoff for gender certainty was used based on existing literature and methodology in similar bibliometric studies. 16,22 A total of 6,824 articles were analyzed for data extraction—3,021 from CORR, 3,077 from JBJS, and 726 from JAAOS. A total of 37 authors' first names were unable to be ascertained, and they were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A 90% cutoff for gender certainty was used based on existing literature and methodology in similar bibliometric studies. 16,22 A total of 6,824 articles were analyzed for data extraction—3,021 from CORR, 3,077 from JBJS, and 726 from JAAOS. A total of 37 authors' first names were unable to be ascertained, and they were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Of the mentee/mentor dyads in our dataset, 94.1% of mentees and 90.09% of mentors had self-identified records of gender. Genderize (genderize.io) was used to assign gender to those without self-identified gender information, as done in previous studies [12, 27, 28]. The agreement between self-identified gender and Genderize was 98%, allowing confidence in using Genderize to populate the small portion of non-self-identified records.…”
Section: Methodsmentioning
confidence: 99%
“…We based our design on several other papers studying gender discrepancies in medical peer-reviewed research and chose to use a gender predicting API because it has been used extensively in research and shown to be accurate. 3,[17][18][19][20][21] We acknowledge that the method of classifying gender is not 100% accurate because of the program's limited ability to classify unisex names. Finally, we recognize the complexity of studying gender and sex, as well as the intersectionality that affects each individuals' experiences and understand that there are many facets to gender equity that are unaddressed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2 While acknowledging this lack of representation, this statistic has been previously attributed to factors, such as limited exposure, lack of quality female mentorship and role models, sex-specific biases, and the perception of a challenging work-life balance. 3 Of the orthopaedic subspecialties, the lowest reported percentage of female physicians are seen in arthroscopy (0.7%), shoulder/elbow (2.4%), and adult spine (3.1%), while the highest percentages are seen in hand (24.0%) and pediatrics (22.6%). 4 Although there is potential for growth in female representation with a rising number of female residents, reducing this gender difference requires both time and continued intentional effort.…”
mentioning
confidence: 96%